Method for the Solution of Interval Systems of Linear Equations - Sarangam Majumdar; S Chakraverty (International Journal of Advances in Applied Sciences, 2013)
System of linear equation (crisp) can be solved in a various way .In the real world problem parameters are in interval form .In this paper we discuss the solution of interval system of linear equations and proposed a new method for handling this type of system of linear equations. In this model we consider the coefficient matrix and the right vector as interval. Example problems are given to have the efficiency and powerfulness of the proposed method.